Essential Per- and Polyfluoroalkyl Substances (PFAS) in Our Society of the Future - Rudy Dams; Bruno Ameduri (Molecules)
Per- or polyfluoroalkyl substances (PFASs) are man-made compounds involved in compositions of many industrial processes and consumer products. The largest-volume man-made PFAS are made up of refrigerants and fluoropolymers. Major concerns for our society related to these substances are their contribution to global warming as greenhouse gasses and the potential for adverse effects on living organisms, particularly by long-chain perfluoroalkyl acid derivatives. Restrictions on manufacturing and applications will increase in the near future. The full remediation of historical and current contaminations of air, soil and water remains problematic, especially for ultra-short PFASs, such as trifluoroacetic acid. Future monitoring of PFAS levels and their impact on ecosystems remains important. PFASs have become integrated in the lifestyle and infrastructures of our modern worldwide society and are likely to be part of that society for years to come in essential applications by closing the fluorine loop.